BIOTECHNOLOGICAL KINETIC ANALYSIS OF HYDROLYZED STARCH BY SACCHAROMYCES CEREVISIAE MEYEN EX E.C. HANSEN - Marín-Machuca, Olegario (2020)
The study describes the biotechnological process, a product of the hydrolyzed starch's fermentation using Saccharomyces cerevisiae Meyen ex E.C. Hansen as an enzyme agent. The behavior and speeds of the three intervening components (consumed substrate [Sc], product [P], and enzymatic agent [E]) were evaluated and was formulated the corresponding logistic models, independently, for each of the components and their subsequent application and analysis. Also, the saturation constant of the substrate [Km] was determined. The maximumconcentration for the enzyme reached a value of 9.80 g·L-1, and the reaction rate constants were 0.27 h-1, 0.20 h-1, and 0.22 h-1, for the concentrations of E, Sc, and P, respectively. The maximum speeds (and the optimal times) for the enzyme, substrate consumed, and product were 0.66 gL-1h-1 (6.80 h), 6.68 gL-1h-1 (11.50h), and 3,15 gL-1h-1 (11.40h), respectively. The saturation constant Km for the consumed substrate, both by the Lineweaver-Burk equation and graph, and the Monod graph and theory, reached the values of 12.44 g·L-1 and 11.50 g·L-1, respectively. It is concluded that the proposed biotechnological kinetic analysis of the hydrolyzed starch by S. cerevisiae is adequate. Keywords: biotechnology – fermentation – kinetics – logistics model – saturation constant